Pengaruh Pola Makan terhadap Kejadian Dismenore pada Remaja - Azzahra, Florin; Ambarwati, Dewi; Pangesti, Wilis Dwi (Jurnal Riset Kesehatan Masyarakat, 2023)
Adolescence is a stage or phase between childhood and adulthood. Growth and development in adolescence is very fast both physically and psychologically. The reproductive organs in women begin to function with one of the characteristics, namely the start of menstruation. In general, women experience menstruation accompanied by pain or dysmenorrhea. Dysmenorrhea is a gynecological complaint caused by an imbalance of the hormone progesterone which causes pain. There are many causes of dysmenorrhea, one of which is diet. Adolescents who have poor nutritional status can cause disruption of the function of the reproductive organs. One way to prevent menstruation from causing pain is by consuming a balanced nutritional diet. This literature review aims to determine the relationship between diet and the incidence of dysmenorrhea in adolescents. The type of research used is a literature review with a descriptive method. This literature review uses articles or journals that can be accessed in full text. These results were obtained in 5 journals which stated that diet and the incidence of dysmenorrhea had a significant relationship. 4 journals stated that diet had no significant relationship with the incidence of dysmenorrhea and 6 journals mentioned other factors that cause dysmenorrhea and the impact of dysmenorrhea itself. The relationship between diet and the incidence of dysmenorrhea depends on a person's nutritional status.